Implementasi Konseling Humanistik Bagi Warga Binaan Pengedar Narkoba Lapas Banyuwangi - N, Syakiratun.; Yohandi; Sulaiman, A. Husam (Jurnal Ilmu Bimbingan dan Konseling, 2025)
Inmates (specifically in Sritanjung) involved in drug trafficking cases often face a dual stigma: as criminals and as "destroyers of society." This negative labeling impacts the self-concept and leads to a loss of meaning in life, which in turn triggers recidivism. This community service (dedication/project) aims to restore the self-esteem and self-potential awareness of inmates involved in drug trafficking through the implementation of humanistic counseling. This approach was chosen because it focuses on unconditional positive regard and self-actualization. The implementation method uses Participatory Action Research (PAR) with the stages of building (rapport), exploring feelings, digging for insight (potential), and action planning. The subject of this project was one inmate categorized as a drug trafficker at Lapas Kelas IIA Banyuwangi (Banyuwangi Class IIA Penitentiary/Correctional Institution). The results show a significant increase in (self-acceptance). The inmate, who initially felt worthless and ostracized, began to see positive potential within themselves to live a new, productive life post-release. The contribution of this activity is the strengthening of a humanistic coaching model in the Penitentiary, one that not only punishes but also restores human dignity.